Attention deficit hyperactivity disorder: towards an inclusive approach in the management of ADHD in South African classrooms - Loedolff, Simone (School of Education, 2020)
Attention Deficit Hyperactivity Disorder (ADHD) is a world-wide phenomenon which has a major impact not only on a child’s academic performance but also daily activities and social interactions. It is a phenomena which manifests in most classrooms. This dissertation investigates ADHD, not only as a medical phenomenon, but also as a social phenomenon, with a specific focus on how it manifests and applies in South African schools. Using Vygotsky’s Cultural Historical Activity Theory, and linking it with the ideals of the Education White Paper 6. The research is presented as a literature review that focuses on what current literature suggests is happening, and what theoretically should be happening in practice. The research is intended to demonstrate the need of the school-going aged child to be supported by the family, the school, and, if chosen, by medical professionals as well as the need to have informed parents and teachers. This need is linked to an exploration in this research of the practices and procedures currently being used to support learners with ADHD in mainstream South African schools in the context of an inclusive education model. The research concludes that Educators needs further support and training to be fully equipped to support learners formally and informally diagnosed with ADHD.